Caracterização e avaliação dos padrões de resistência antimicrobiana no bacterioma da bacia do Rio Jaguaribe (Ceará, Brasil) - Martins, Sandra Rebeca Oliveira (2023)
The World Health Organization (WHO) considers the spread of resistance genes among bacteria to be one of the main and most serious global public health problems. The number of microorganisms in aquatic environments that carry genes directly linked to resistance to antimicrobials resulting from the pressure exerted by anthropogenic activities and actions is increasing. The occurrence of residues of antibiotic substances in the environment ends up favoring the selection of bacterial strains resistant to antibiotic agents and greater circulation of resistance genes in environmental matrices. In addition to the irresponsible use of antimicrobials, other anthropogenic stressors can contaminate soil and surface waters and contribute to resistance profiles of bacterial communities. Thus, the main objective of the research was to characterize the bacterial resistance phenotypes related to water and sediment along the Jaguaribe River basin, in Ceará, correlating with the anthropogenic activities present in its surroundings. Water and sediment were collected at six different points along the river. Dilutions of the samples were inoculated into conventional culture medium Standard Counting Agar (PCA) using the Pour Plate technique. Then, the colony-forming units were quantified, isolated, identified and subjected to antibiogram and plasmid cure tests. Eight antibiotics were tested: Tetracycline, Doxycycline, Sulfazotrim, Erythromycin, Azithromycin, Levofloxacin, Chloramphenicol and Ampicillin. Bacterial counts were expressed in colony forming units (CFU) and ranged from 7.88 x 106 to 1.67 x 107 CFU/ml for water samples and from 2.09 x 104 to 1.96 x 106 CFU /g for sediment samples. Among bacterial cultures, Gram-positive bacteria were more frequently isolated than Gram-negative bacteria. Of the total isolates, 82% were resistant to one or more antimicrobials and 18% were sensitive to all antibiotics tested. The most frequent resistance phenotypes among bacterial isolates were against the substances Ampicillin (54%), Doxycycline (34%) and Tetracycline (28%) and the largest number of isolates expressing resistance was detected in water samples. The genetic origin of resistance was, for the most part, potentially chromosomal. The percentages of antimicrobial resistance observed in the bacteriota of sections of the Jaguaribe River basin indicate the effect of selective pressure related to the activities in its surroundings.